DIVERSITY AND PHENETIC STUDY ON SYCONIUM OF FICUS L. (MORACEAE) FROM KERALA, INDIA REVEALING NATURAL CLASSIFICATION ALONG WITH AN IDENTIFICATION KEY - Sreehari S Nair; K.H. Amitha Bachan; P.J. Ebin (Research Center for Biology, 2021)
NAIR, S. S., BACHAN, K. H. A. & EBIN, P. J. 2021. Diversity and phenetic study on syconium of Ficus L. (Moraceae) from Kerala, India revealing natural classification along with an identification key. Reinwardtia 20(1): 27–36. — Ficus L. commonly called ‘figs’ is one of the most complex genera among the angiosperms with its specialised inflorescence called syconium that looks like a fruit. Syconium of 33 species of Ficus reported from Kerala were observed here to develop a novel key, solely based on syconium morphology. Numerical taxonomic methodology for syconium morphological characters were standardised, considering 22 characters with 104 character states and analysed using similarity clustering. The floral features of the genus are very much complex and all the existing keys for the species identification relays on both vegetative as well as floral features. Hence, the present key will be practical in use when syconium is the only available part. The numerical analysis of the syconium features well clustered and separated the trees with cauliflorous inflorescence, hemi epiphytic -epiphytic life forms and independent trees similar to the natural classification of the figs as “Atthi, Itthi and Aal”, indicating that phenetic analysis using the syconium characters alone provided a grouping similar to the natural grouping based on the habit. Preliminary phylogenetic analysis of figs also provided a similar clustering. This gives an insight into the fact that the separation of figs into these natural groups is reflecting phylogenetic trait. Detailed studies including more morphological traits and molecular analysis could establish the phylogenetic relation of figs in relation to the evolutionary history of climate and vegetation.